Reminiscencia y prospección de futuro en adultos mayores - Montenegro, Pedro Jaime García (2021)
Autobiographical memory and reminiscence are the bases on which personal narratives are built, communicative resources that fulfill functions associated with the Self, but also coordinate and enrich interactions with others. In turn, projecting the future time reinforces our purposes and vital determinations. The objective of this research was to explain the subjectivity of future prospecting (a precept of the social world) based on autobiographical narratives (reminiscences) produced by the elderlies after participating in a cognitivecommunicative stimulation program. This research assumed a mixed methodology in its course; since initially evidence was obtained of the effect on global cognitive efficacy and subjective well-being of a cognitive-communicative stimulation program based on reminiscence (PECC-R); subsequently, a proposal for an autobiographical interview was developed and the reason for its content validity was obtained, highlighting the clinical projections that this instrument has for the Speech and Language practice with the elderly population. Finally, from a qualitative perspective, the phenomenology of the relationship between reminiscence and prospection in the aging of typical older people was studied through autobiographical narratives. Theoretically, the paradigm of Interpretative Phenomenological Analysis is adhered to for these purposes since it was sought to explain a precept of the social world (prospection) from autobiographical narratives (reminiscences). The usefulness of reminiscence as a valid tool for the analysis and interpretation of the future perspectives developed by the elderly is evident. It is expected that, based on the data produced, the designs of Speech and Language interventions will be restructured and rethought, incorporating this new knowledge to the evaluative and therapeutic actions, rescuing the intersubjectivity inherent to aging to facilitate the interaction with this age people, their groups and/or with other members of the health team interested in them.